Stress fractures: Diagnosis and Management in the primary care setting - Patel, D. R. (Pediatric Clinics of North America, 2010)
Stress fracture represents an overuse injury of the bone resulting from excessive repetitive stress. Diagnosis in most cases is based on clinical evaluation. Plain radiographs may show characteristic changes 2 to 4 weeks from onset of symptoms. Increasingly, magnetic resonance imaging is recognized as the study of choice in the evaluation of stress injury of the bone. Most stress fractures at low-risk sites can be managed in the primary care setting with conservative measures. From a primary care perspective, orthopedic or sports medicine consultation is considered for stress fractures at high-risk sites. This article reviews general principles of diagnosis and management of stress fractures in adolescents.